2013
DOI: 10.1080/11263504.2013.772923
|View full text |Cite
|
Sign up to set email alerts
|

Effect of environmental conditions on decomposition in eight woody species of a dry tropical forest

Abstract: Litter decay is a significant part of carbon budget. Due to strong environmental control, the changes in the environment may drastically influence the litter decay rates. Litter decomposition of eight dry tropical woody species, viz. Shorea robusta, Buchanania lanzan, Diospyros melanoxylon, Lagerstroemia parviflora, Lannea coromandelica, Terminalia tomentosa, Holarrhena antidysenterica and Lantana camara was studied to document the effect of intra-annual changes in the environment. Litter decomposition was mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 62 publications
(62 reference statements)
1
5
0
Order By: Relevance
“…Several factors such as litter quality, nutrient requirements of the microbial biomass (Seastedt 1984) and exogenous nutrient availability (Berg et al 1987) affect decomposition and nutrient release. Nitrogen is one of the main limiting nutrients for microbial growth and its low value in the beech litter (mean content: 0.6 -1.3%) caused a low decomposition rate (Gregori et al 1991;Pandey et al 2014). In our study, the increase in litter N content during decomposition, together with Fe, Zn, Na, S, K and Mn, evidenced their immobilization suggesting that these nutrients were limiting for micro-organism growth.…”
Section: Discussionmentioning
confidence: 47%
“…Several factors such as litter quality, nutrient requirements of the microbial biomass (Seastedt 1984) and exogenous nutrient availability (Berg et al 1987) affect decomposition and nutrient release. Nitrogen is one of the main limiting nutrients for microbial growth and its low value in the beech litter (mean content: 0.6 -1.3%) caused a low decomposition rate (Gregori et al 1991;Pandey et al 2014). In our study, the increase in litter N content during decomposition, together with Fe, Zn, Na, S, K and Mn, evidenced their immobilization suggesting that these nutrients were limiting for micro-organism growth.…”
Section: Discussionmentioning
confidence: 47%
“…) and other environmental conditions, such as the temperature (Pandey et al . ). Studies that compared the soil pH and bacterial activity concluded that acidic soils might inhibit both the bacterial and the fungal activity in the soils (Rousk et al .…”
Section: Discussionmentioning
confidence: 97%
“…Litter decomposition is an important process that connects many above‐ and below‐ground processes (Pandey et al . ). Some previous studies have shown that invasive alien plants, such as Lantana camara , Eucalyptus and Acacias , increase the amount of soil nutrients (especially soil N, P and C), soil pH, microbial N and P, decomposition rates and soil water repellency (Ehrenfeld ; Fan et al .…”
mentioning
confidence: 97%
“…In Sefwi Wiawso and Sefwi Juaboso the difference in SOC was as a result of high litter accumulation in the fields which serves as the primary source of SOC (Post & Kwon, 2000). This high litter fall aided by good environmental conditions for decomposition, thus, soil surface temperature and soil moisture (Pandey et al, 2013), caused variations in the SOC stored (Post & Kwon, 2000).…”
Section: Effect Of Shade Typementioning
confidence: 99%